Method for producing a copper foil by electroplating, current collector, battery and electromagnetic shielding material

CN116590759BActive Publication Date: 2026-10-27BEIHANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310324106.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-29
Publication Date
2026-10-27
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

[0005]本发明的目的在于针对现有超薄金属铜箔难以制备的技术难题,提供了一种电镀法制备金属铜箔的方法

Benefits of technology

[0052]现有技术采用物理气相沉积步骤是在聚合物基体上磁控溅射或者蒸镀上金属铜原子,以该些铜原子为后续电镀铜成核点位生长得到超薄铜基层,但是该些点状铜原子在聚合物基体上难以形成完全覆盖,也即存在非导电的聚合物基体间隙暴露(或称孔洞缺陷),导致后续电镀过程中该些间隙暴露或孔洞缺陷无法沉积金属铜,从而使生长得到超薄铜层的表面也存在间隙/孔洞缺陷,影响超薄铜层的性能及应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116590759B_ABST
    Figure CN116590759B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing a metal copper foil by an electroplating method, a current collector, a battery and an electromagnetic shielding material, wherein the method for preparing the metal copper foil by the electroplating method comprises the following steps: a loading step, in which a MXene material is loaded on at least one side of a surface of a substrate to form a conductive MXene layer; an electroplating step, in which a surface of the conductive MXene layer is subjected to electroplating treatment to form an electroplated copper layer; and a stripping step, in which the substrate is stripped after the loading step and before the electroplating step, or the substrate is stripped after the electroplating step. The metal copper foil prepared by the method of the application is obtained by surface electroplating deposition and growth of the electroplated copper layer on the surface of the conductive MXene layer, and after the substrate is stripped, an ultrathin metal copper foil can be obtained. The conductive MXene layer in the application also plays a role of a stripping transition layer, and greatly simplifies the preparation process of the ultrathin metal copper foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new materials, and in particular relates to a method for preparing copper foil by electroplating, a current collector, a battery, and an electromagnetic shielding material. Background Technology

[0002] Copper foil is one of the fundamental materials in the electronics industry, widely used in industrial lithium-ion batteries, communication equipment, consumer electronics, automotive electronics, electronic shielding, and other fields, with a growing trend towards thinner and lighter designs. Taking copper foil for lithium-ion batteries as an example, as people pursue higher energy density, lighter weight, and greater flexibility in batteries, the thickness of the negative electrode current collector copper foil has gradually decreased from 12μm to 4.5μm. The thinner the copper foil, the better its ability to carry the negative electrode active material, resulting in a larger battery capacity and lighter weight, thus providing higher energy density. However, further thinning of the copper foil reduces its mechanical strength, leading to decreased processing performance. Traditional electrolytic and rolling copper foil technologies struggle to obtain ultra-thin copper foil (thickness < 4.5μm).

[0003] To obtain ultrathin copper foil, polymer film-based composite copper foil current collectors have attracted attention and application. Conventional composite copper foil current collectors typically include a polymer film layer and a copper substrate formed on the polymer film layer by methods such as physical vapor deposition (PVD). The corresponding preparation process usually includes: (1) depositing a layer of copper on the polymer film using physical vapor deposition (magnetron sputtering or evaporation) to prepare a composite copper current collector semi-finished product with certain conductivity; (2) further processing the composite copper current collector semi-finished product using electroplating to prepare the composite copper current collector. Compared with traditional current collectors (electrolytic copper foil), polymer film-based composite copper current collectors have the characteristics of low cost, light weight, and good internal insulation. These characteristics enable the composite copper current collector to reduce the cost of secondary batteries and improve the energy density and safety of batteries when used in secondary batteries.

[0004] However, in composite copper foil current collectors made of polymer films, the copper layer deposited on the polymer film by physical vapor deposition has a strong bond with the polymer, making it difficult to peel off the electroplated copper foil to obtain ultra-thin copper foil. To address this technical problem, patent application CN115058711 B discloses a method using copper foil as a carrier, followed by magnetron sputtering treatment, the application of an organic release layer, and then electroplating to deposit copper. However, this method requires magnetron sputtering equipment, is complex, energy-intensive, and costly, making it difficult to implement in practice. Summary of the Invention

[0005] The purpose of this invention is to address the technical challenge of preparing ultra-thin copper foil by providing a method for preparing copper foil using electroplating.

[0006] The first aspect of the present invention provides a method for preparing copper foil by electroplating, comprising the steps of: a coating step: coating an MXene material onto the surface of at least one side of a substrate to form a conductive MXene layer; an electroplating step: electroplating the surface of the conductive MXene layer to form an electroplated copper layer; and a peeling step: peeling the substrate after the coating step and before the electroplating step; or, peeling the substrate after the electroplating step.

[0007] In some embodiments, the above coating steps may include more specific steps such as: coating and / or spraying an MXene dispersion onto the surface of the substrate, drying to form the conductive MXene layer; and / or lifting and / or impregnating the substrate from the MXene dispersion, drying to form the conductive MXene layer.

[0008] In some embodiments, the MXene dispersion described above does not include binders and / or dispersants.

[0009] In some embodiments, the above-mentioned MXene dispersion is composed of MXene material and a solvent; preferably, the solvent is selected from water and / or alcohols;

[0010] In some embodiments, the concentration of MXene in the above-mentioned MXene dispersion is between 0.1 mg / ml and 80 mg / ml.

[0011] In some embodiments, the thickness of the conductive MXene layer is between 3 nm and 50 μm; and / or, the thickness of the copper substrate is between 10 nm and 100 μm; and / or, the thickness of the substrate is between 1 μm and 50 μm.

[0012] In some embodiments, the thickness of the copper substrate is between 100 nm and 10 μm, preferably between 0.5 μm and 4 μm; more preferably between 1 μm and 3 μm.

[0013] In some embodiments, the thickness of the conductive MXene layer is between 10 nm and 5 μm.

[0014] In some embodiments, the substrate is a non-conductive material.

[0015] In some embodiments, the non-conductive material is selected from polymers, ceramics, or glass.

[0016] In some embodiments, the polymer is selected from one or more of acrylonitrile-butadiene-styrene copolymer, polysulfone, polycarbonate, polypropylene, phenolic resin, phenolic glass fiber reinforced plastic, nylon, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyimide, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene ether, polystyrene, polyamide, and derivatives of the above polymers.

[0017] In some embodiments, the preparation method further includes a passivation step: passivating the surface of the copper substrate to form a protective layer.

[0018] A second aspect of the present invention provides a copper foil obtained by the above-described electroplating method for preparing copper foil.

[0019] In some embodiments, the thickness of the copper foil is between 100 nm and 100 μm; more preferably, the thickness of the copper foil is between 1 μm and 10 μm; and even more preferably, the thickness of the copper foil is between 1 μm and 5 μm.

[0020] A third aspect of the present invention provides a copper foil comprising a copper substrate and an MXene layer, wherein the copper substrate is formed by electroplating copper onto the surface of the MXene material.

[0021] In some embodiments, the thickness of the copper substrate is between 10 nm and 100 μm; preferably, the thickness of the copper substrate is between 100 nm and 10 μm, more preferably, the thickness of the copper substrate is between 0.5 μm and 4 μm; even more preferably, it is between 1 μm and 3 μm.

[0022] In some embodiments, the thickness of the conductive MXene layer is between 3 nm and 50 μm; preferably, the thickness of the conductive MXene layer is between 10 nm and 1 μm.

[0023] In some embodiments, the aforementioned copper foil has one or two copper substrate layers.

[0024] A fourth aspect of the present invention provides a copper current collector, wherein the preparation method of the copper current collector includes the method for preparing copper foil by the electroplating method described above; or, the copper current collector includes the copper foil described above.

[0025] In some embodiments, the thickness of the aforementioned copper current collector is between 1 μm and 10 μm; preferably, the thickness is between 1 μm and 5 μm.

[0026] A fifth aspect of the present invention provides an electrode sheet comprising the aforementioned copper current collector.

[0027] A sixth aspect of the present invention provides a battery comprising the aforementioned copper current collector; or the aforementioned electrode sheet.

[0028] A seventh aspect of the present invention provides an electromagnetic shielding material, wherein the method for preparing the electromagnetic shielding material includes the method for preparing copper foil by the electroplating method described above; or, the electromagnetic shielding material includes the copper foil described above.

[0029] In some embodiments, the thickness of the electromagnetic shielding material is between 1 μm and 100 μm.

[0030] The eighth aspect of the present invention provides an application of MXene material at the interface of a polymer as an electroplating layer and / or a separation medium.

[0031] This invention forms a conductive MXene layer on a substrate using simple coating, spraying, and / or immersion methods, and then electroplats copper on the surface of the MXene layer. During the copper electroplating process, the MXene material acts as a nucleating agent to obtain the electroplated copper layer. The substrate is then peeled off to obtain a metallic copper foil.

[0032] The copper foil obtained by the preparation method of the present invention is obtained by surface electroplating deposition of a copper layer on the surface of a conductive MXene layer. After peeling off the substrate, a copper foil can be obtained. The conductive MXene layer in the present invention also serves as a peeling transition layer, which greatly simplifies the preparation process of ultrathin copper foil. Attached Figure Description

[0033] Figure 1 This is a schematic diagram of the substrate stripping step and the resulting copper foil structure in the electroplating method for preparing copper foil according to Embodiment 1 of the present invention.

[0034] Figure 2 This is a schematic diagram of the substrate stripping and electroplating steps and the resulting copper foil structure in the electroplating method for preparing copper foil in Embodiment 2 of the present invention.

[0035] Figure 3 This is a photograph of the separated matrix on the PET / MXene / Cu composite in Example 3 of the present invention.

[0036] Figure 4 This is a photograph of the thickness test of the copper foil in Embodiment 3 of the present invention.

[0037] Figure 5 The images show (a) a SEM image of the surface of the copper foil obtained in Example 3 of this invention, and (b) elemental distribution images of Ti, F, and Cu.

[0038] Figure 6This is a cross-sectional SEM image of the conductive MXene layer and the electroplated copper layer in the copper-metal composite current collector of Embodiment 4 of the present invention.

[0039] Figure 7 The images show (a) a cross-sectional SEM image and (b) a surface SEM image of the copper foil in Embodiment 5 of the present invention.

[0040] Figure 8 This is a schematic diagram of the structure of the MXene two-dimensional sheet of the present invention forming an ultrathin conductive MXene layer on the substrate surface.

[0041] Figure 9 (a) Cross-section and (b) Surface SEM images of copper electroplated on the graphene layer in Comparative Example 1 of this invention.

[0042] Figure 10 This is a schematic diagram of the structure of the lithium metal electrode sheet containing the copper foil of the present invention in Embodiment 7 of the present invention.

[0043] Explanation of key figure labels:

[0044] 100 composite; 110, 120 copper foil; 200 electrode sheet;

[0045] 10 Substrate; 20 Conductive MXene layer (or MXene layer); 21 MXene two-dimensional sheet; 30 Electroplated copper layer; 40 Lithium base layer. Detailed Implementation

[0046] The technical solution of the present invention is illustrated below through specific embodiments. It should be understood that the one or more steps mentioned in the present invention do not preclude the existence of other methods and steps before or after the combined steps, or that other methods and steps may be inserted between these explicitly mentioned steps. It should also be understood that these examples are for illustrative purposes only and are not intended to limit the scope of the present invention. Unless otherwise stated, the numbering of each method step is only for the purpose of identifying each method step, and not for limiting the order of each method or limiting the scope of the present invention. Changes or adjustments to their relative relationships, without substantial changes to the technical content, can also be considered as within the scope of the present invention.

[0047] The MXene material and graphene used in this embodiment of the invention were purchased from Jinan Sanchuan New Material Technology Co., Ltd., wherein Ti3C2T x The slurry product model is SC02003LW, with concentrations of 5 mg / ml and 50 mg / ml. This Ti3C2T... x The slurry contains two-dimensional MXeneTi3C2T x MXene was obtained by etching the Al layer of the MAX phase material Ti3AlC2 followed by ultrasonic exfoliation. The MXene powder was made from Ti3C2T. xThe graphene in the comparative example was prepared by redox method at a concentration of 0.5 wt.%.

[0048] The raw materials and instruments used in the examples are not subject to any specific restrictions on their source; they can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0049] In preparing composite copper current collectors using conductive MXene layers, the following properties and characteristics were discovered: 1) The MXene layer exhibits excellent compatibility with the electroplating solution, primarily due to the abundance of hydrophilic functional groups such as -OH and -O on the MXene surface; 2) The use of MXene can significantly reduce the deposition overpotential of metallic copper, as the abundant surface functional groups of MXene become nucleation sites for copper; 3) MXene materials enable uniform deposition and growth of metallic copper ions on their surface, thanks to the high conductivity and high specific surface area of ​​MXene, which greatly homogenizes the electric field and ion flow distribution during the electroplating process; 4) A dense, ultrathin copper layer and an ultrathin composite current collector were obtained on the MXene material, due to the atomically thin two-dimensional structure of MXene, which significantly reduces the thickness of the composite current collector; 5) The conductive MXene layer can also serve as a separation layer, easily peeled off from the polymer matrix, solving the technical problem of separating the matrix using methods such as vapor deposition or magnetron sputtering.

[0050] Since the copper foil obtained by the method of the present invention is obtained after peeling off the substrate, MXene material can inevitably be detected on or within the surface of the copper foil. That is, the copper foil has a technical feature of containing MXene material. When the copper foil obtained by the present invention is used as the negative electrode current collector of a lithium-ion battery, the MXene material on the surface of the copper foil can also serve as nucleation sites for lithium metal, reducing the nucleation overpotential of lithium metal and enabling the controlled nucleation and growth of lithium metal into a blunt lithium metal block (pebble-shaped), thereby avoiding the formation of sharp lithium metal dendrites.

[0051] The advantages of the copper foil obtained by the present invention compared with the ultrathin copper layer obtained by the physical vapor deposition process in the prior art are as follows:

[0052] Existing technologies employ physical vapor deposition (PVD) to magnetron sputter or vapor-deposit copper atoms onto a polymer substrate. These copper atoms then serve as nucleation sites for subsequent copper electroplating, resulting in the growth of an ultrathin copper substrate. However, these dot-shaped copper atoms are difficult to completely cover the polymer substrate, meaning that there are exposed gaps (or pores) in the non-conductive polymer substrate. This prevents the deposition of copper atoms during subsequent electroplating, resulting in gaps / pores on the surface of the grown ultrathin copper layer, which affects the performance and applications of the ultrathin copper layer.

[0053] The copper foil prepared by the method of this invention uses a two-dimensional MXene material as a nucleating agent. The stacked layers of the two-dimensional MXene material can completely cover the substrate, avoiding the exposure of non-conductive substrate gaps or void defects. The copper foil grows based on the nucleation of the two-dimensional MXene sheets, resulting in a dense and smooth electroplated copper layer, which significantly improves the surface smoothness of the copper foil. The technical features of this invention are further illustrated below through specific embodiments.

[0054] Example 1

[0055] This embodiment provides a method for preparing copper foil by electroplating and a copper foil product, such as... Figure 1 The steps shown include:

[0056] S01 Coating Step: Coating the substrate 10 with MXene material to form a conductive MXene layer 20;

[0057] S02 electroplating step: Electroplating deposition is performed on the surface of the conductive MXene layer 20 to obtain an electroplated copper layer 30, thus obtaining a substrate / MXene / copper layer composite 100.

[0058] S03 stripping step: The substrate 10 in the substrate / MXene / copper layer composite 100 is stripped to obtain the metal copper foil 110 of the present invention.

[0059] In this embodiment, one side of the conductive MXene layer 20 is in contact with the substrate 10, and the other side is electroplated with metallic copper to form an electroplated copper layer 30. After the substrate 10 is peeled off, the conductive MXene layer 20 will inevitably be present on one side of the obtained copper foil 110. That is, the method of this embodiment yields a copper foil with one side being metallic copper and the other side being a copper foil containing MXene material.

[0060] In another embodiment, the substrate is coated with a conductive MXene layer and an electroplated copper layer on both sides.

[0061] Example 2

[0062] This embodiment provides another method for preparing copper foil by electroplating and a copper foil product, such as... Figure 2 The steps shown include:

[0063] S11 Coating Step: Coating the surface of the substrate 10 with MXene material to form a conductive MXene layer 20;

[0064] S12 stripping step: The conductive MXene layer 20 is stripped from the substrate 10 to obtain the conductive MXene layer 20;

[0065] S13 Electroplating step: Electroplating the surface of the conductive MXene layer 20 to form an electroplated copper layer 30.

[0066] In this embodiment, an independent conductive MXene layer 20 is first prepared by substrate 10, and then the conductive MXene layer 20 is placed in an electroplating device to electroplat metallic copper on both sides of the conductive MXene layer 20 to obtain a composite metallic copper foil 120 with a copper / MXene / copper "sandwich" structure.

[0067] In steps S01 and S11, the method for coating the substrate with MXene material to form a conductive MXene layer can be either a dry process or a wet process. The dry process involves forming a film layer on the surface of the substrate using MXene powder and binders under solvent-free conditions. The wet process involves coating the substrate surface with an MXene dispersion through spraying, dipping, or coating methods, and then drying to remove the solvent to form a conductive MXene layer. The dry process avoids the solvent removal step, simplifying the process flow. However, forming a stable and continuous conductive layer requires the addition of a binder; non-conductive binders reduce the continuous conductivity of the conductive MXene layer surface. Therefore, the wet process is preferred. The wet process also allows for a more uniform dispersion of the MXene material on the substrate surface. Although it includes a solvent removal step, due to the good hydrophilicity of MXene, aqueous solvents (including water and / or alcohol solvents) are typically used, which are low-cost and easy to remove. In one specific embodiment, the method includes: coating the surface of a substrate with an MXene dispersion by spraying and / or coating it once or several times to form an MXene film, and then drying it to form a conductive MXene layer; in another specific embodiment, the method includes: repeatedly lifting and / or immersing the substrate in the MXene dispersion to allow the two-dimensional MXene sheets in the dispersion to be oriented and continuously coated on the surface of the substrate under the action of surface tension, and then drying it to form a conductive MXene layer.

[0068] The substrate material can be selected from metal, polymer, or inorganic non-metal (such as ceramic, glass, etc.). Since the main function of the substrate is to serve as a carrier for the spread of the conductive MXene layer, the type of substrate material is not limited. Polymer substrate is preferred because polymer materials are relatively soft, making it easy to adjust the surface roughness. They are also inexpensive and easy to mold.

[0069] Optionally, the polymer matrix material includes one or more of polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polyimide (PI), polypropylene, polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), polyphenylene oxide (PPO), polystyrene (PS), polyamide (PA), and derivatives of the above polymers.

[0070] Figure 1 A copper foil 110 with an electroplated copper layer 30 on one side of a conductive MXene layer 20 is provided. Figure 2 A copper foil 120 with a conductive MXene layer 20 and copper-plated layers 30 on both sides is provided. It should be noted that the thickness of the copper-plated layers 30 can be the same or different when the copper layers are plated on both sides.

[0071] Example 3

[0072] This embodiment provides a metallic copper foil and its preparation method. In this embodiment, a high-concentration MXene dispersion (50 mg / ml) is coated onto a polymer PET film using a doctor blade. More specific steps include:

[0073] (1) Prepare Ti3C2T with a mass concentration of 50 mg / ml x Aqueous dispersion (viscous slurry), wherein the solvent is water and there is no binder;

[0074] (2) The Ti3C2T x An aqueous dispersion is coated onto one side of a PET film using a doctor blade to form a Ti3C2T layer. x The Ti3C2T membrane can be easily controlled by the gap between the doctor blade and the PET film. x The thickness of the film was determined by vacuum drying at 50°C for 4 hours to form a conductive MXene layer, resulting in a PET / MXene composite layer.

[0075] (3) The dried PET / MXene composite layer is placed in an electroplating apparatus for electroplating treatment. The specific electroplating process steps include:

[0076] a. Electroplating solution formulation for electrodeposition of copper: copper sulfate pentahydrate with a copper ion concentration of 80 g / L, concentrated sulfuric acid of 100 g / L, concentrated hydrochloric acid of 15 mg / L, polyethylene glycol (PEG) of 5 mg / L, hydroxyethyl cellulose (HEC) of 8 mg / L, sodium polydithiopropane sulfonate (SP) of 3 mg / L, and collagen of 10 mg / L.

[0077] b. At an operating temperature of 50℃ and a current density of 9A / dm 2 Under the conditions of 2V DC electrodeposition for 30s, an electroplated copper layer is formed on the surface of the PET / MXene composite layer. After cleaning and drying, the composite PET / MXene / Cu is obtained.

[0078] For ease of demonstration, in the electroplating step of this embodiment, half of the PET / MXene composite layer is placed in the electroplating apparatus for copper electroplating, and the resulting product is shown in the photograph. Figure 3As shown, the black half is a PET / MXene composite layer, where the black layer is a conductive MXene layer; the other half, copper-colored, is an electroplated copper layer. The substrate PET layer can be easily separated from the composite PET / MXene / Cu using tweezers. Figure 4 The copper foil of the present invention was obtained by means of a thickness gauge. The copper foil is intact and has a smooth surface. The thickness of the obtained copper foil is only 7 μm, as measured by a thickness gauge.

[0079] Figure 5 Image a shows an SEM image of the surface of the copper foil, revealing a smooth and flat electroplated copper layer. Since the method of this invention obtains the copper foil by peeling off the substrate, MXene material is inevitably detectable on the surface of the copper foil. Figure 5 Elemental analysis (EDS) of the copper foil surface is shown in b-c, revealing the presence of Ti and F elements of MXene in the electroplated copper layer, confirming the presence of MXene material. In other words, the copper foil of this invention possesses a technical characteristic: it contains MXene material on its surface or internally. Elemental analysis tests can detect the presence of M and functional group elements within the MXene material.

[0080] Example 4

[0081] This embodiment provides another copper foil and its preparation method, similar to Example 3, except that the MXene dispersion is sprayed onto the substrate PP film by a spraying method, and the copper electroplating time is different. More specific preparation methods include:

[0082] (1) Prepare Ti3C2T with a mass concentration of 1 mg / ml x Aqueous dispersion (solvent is water, no binder);

[0083] (2) The dispersion was sprayed onto one or both sides of a PP film with a thickness of 10μm using a sprayer. After air drying, it was placed in a vacuum oven and vacuum dried at 50℃ for 4h to obtain a PP / MXene composite layer.

[0084] (3) The dried PP / MXene composite layer was placed in an electroplating device for electroplating treatment. The specific electroplating process was similar to that in Example 3, except that the electroplating time was 1 min, and the composite PP / MXene / Cu was obtained.

[0085] (4) Peel off the PP film in the composite PP / MXene / Cu to obtain the metal copper foil of the present invention. Figure 6 A cross-sectional SEM image of the copper foil is provided, showing that the thickness of the conductive MXene layer is about 1 μm and the thickness of the electroplated copper layer is about 2 μm.

[0086] Example 5

[0087] This embodiment provides another metallic copper foil and its preparation method, similar to Example 3, except that the MXene dispersion is coated onto a PET film substrate by an impregnation method. More specific preparation methods include:

[0088] (1) Prepare Ti3C2T with a mass concentration of 2 mg / ml x Aqueous dispersion (solvent is water, no binder);

[0089] (2) Impregnate a 10 μm thick PET film with Ti3C2T x After dispersing the PET film in an aqueous solution, slowly and uniformly lift the film out of the water to allow the Ti3C2T to dissolve. x Two-dimensional Ti3C2T in aqueous dispersion x The surface tension of the aqueous solution is applied to the surface of the PET film. After the PET film is pulled out and air-dried naturally, it is repeatedly pulled up and dried several times (5 times). Then it is placed in a vacuum oven and vacuum dried at 50°C for 4 hours to obtain the PET / MXene composite layer.

[0090] (3) The dried PET / MXene composite layer was placed in an electroplating apparatus for electroplating. The specific electroplating process was similar to that in Example 3, except that the electroplating current was 2A / dm². 2 The electroplating time was 30 seconds, resulting in a copper composite film PET / MXene / Cu.

[0091] (4) Peel the PET film from the copper composite film PET / MXene / Cu to obtain the metal copper foil MXene / Cu.

[0092] Figure 7 The image provided is a cross-sectional SEM image of the copper foil, showing that the thickness of the conductive MXene layer is approximately 1 μm and the thickness of the electroplated copper layer is approximately 1 μm. Figure 7 b presents an SEM image of the surface of the copper composite current collector, which shows that the surface of the electroplated copper layer is smooth and flat. The surface of the electroplated copper layer has the characteristics of being smooth and dense, indicating that high-quality electroplating of copper can be achieved on the surface of the conductive MXene layer.

[0093] Compared to the coating method in Example 3 and the spraying method in Example 4, the dip-coating method in Example 5 can obtain a thinner conductive MXene layer. This is because during the dipping process, the surface tension of the liquid causes the two-dimensional MXene sheets in the MXene dispersion to be oriented and spread evenly onto the surface of the substrate, resulting in a thinner MXene layer that completely covers the substrate surface. Figure 8As shown in the schematic diagram, MXene two-dimensional sheets are laid flat and overlapped on the surface of the polymer film to form an ultrathin MXene layer. The thickness of the MXene layer can be as low as the thickness of several layers of MXene two-dimensional sheets. Since the MXene two-dimensional sheets are also flexible, the ultrathin MXene layer can adhere to the surface of the polymer film.

[0094] By controlling the electroplating process conditions, including temperature, current density, and electroplating time, the thickness range of the electroplated copper layer can be easily controlled. In some embodiments, the thickness of the electroplated copper layer is between 10 nm and 500 μm. When the metal composite film is used as a current collector, preferably, the thickness of the electroplated copper layer is between 1 μm and 4 μm (1 μm ≤ thickness ≤ 4 μm); in a specific embodiment, the thickness of the electroplated copper layer is 3.5 μm, 2.5 μm, 1.5 μm, or 1 μm.

[0095] Example 6

[0096] This embodiment provides another type of copper foil and its preparation method. In this embodiment, a conductive MXene layer is first prepared, and copper is electroplated on the conductive MXene layer to obtain a copper foil with double-sided copper layers. More specific steps include:

[0097] (1) Prepare Ti3C2T with a mass concentration of 50 mg / ml x Aqueous dispersion (viscous slurry), wherein the solvent is water and there is no binder;

[0098] (2) The Ti3C2T x An aqueous dispersion is coated onto one side of a PET film using a doctor blade to form a Ti3C2T layer. x The Ti3C2T membrane can be easily controlled by the gap between the doctor blade and the PET film. x The thickness of the film was determined by vacuum drying at 50°C for 4 hours to form a conductive MXene layer, resulting in a PET / MXene composite layer.

[0099] (3) Peel off the PET film from the dried PET / MXene composite layer to obtain the conductive MXene layer;

[0100] (4) The conductive MXene layer is placed in the electroplating device for electroplating treatment. The specific electroplating process steps are the same as in Example 3. Copper is electroplated and deposited on both sides of the conductive MXene layer to obtain a composite copper foil with a "sandwich structure", wherein the middle is the conductive MXene layer and the two sides are copper layers.

[0101] It should be noted that in this embodiment, Ti3C2T x The main component of the aqueous dispersion is Ti3C2T x And water, that is, Ti3C2Tx Aqueous dispersion composed of Ti3C2T x It is composed of water, but trace amounts of impurities cannot be ruled out. Due to Ti3C2T x It exhibits good hydrophilicity and can be stably dispersed in aqueous solutions, thus eliminating the need for dispersants. Ti3C2T x The MXene layer, formed by the overlapping of micron-sized two-dimensional sheets, leverages the high specific surface area and van der Waals forces of two-dimensional materials to create strong adhesion between the MXene sheets, thus eliminating the need for binders. Conventional dispersants and binders are non-conductive components; their addition to the dispersion would inevitably affect the conductivity of the coated MXene layer, thereby impacting the electroplating effect on the MXene layer surface. Of course, this invention does not preclude the addition of small amounts of binders and / or other functional additives to the MXene dispersion according to practical needs.

[0102] To prevent oxidation of the electroplated copper layer surface, preferably, the preparation method of the present invention further includes a passivation step: passivating the surface of the electroplated copper layer to form a protective layer.

[0103] In Examples 3 to 6, the passivation step specifically includes: after electroplating, the electroplated composite film is placed in a pure water cleaning tank for cleaning, and then passivated in a passivation tank to prepare a surface protective layer. The passivation solution is an aqueous solution of 5 g / L potassium dichromate at a temperature of 25°C. Finally, the cleaned composite film is dried in an oven at a temperature of 70°C.

[0104] In other embodiments, the protective layer for protecting the copper substrate can also be a protective, separable polymer film (such as PP or PE film). These polymer films are attached to the copper composite film prepared above and removed during use.

[0105] Comparative Example 1

[0106] Using a method similar to that in Example 5, the MXene dispersion was replaced with a graphene dispersion to prepare a composite with a conductive graphene layer on the surface of the PET film. Copper electroplating was then performed under the same conditions. The cross-sectional and surface SEM images of the resulting product are shown below. Figure 9 As shown, it is difficult to achieve dense electroplating of metallic copper on the surface of graphene layer. The bonding force between metallic copper and graphene layer is poor, the plating layer is easy to peel off, the surface of electroplated copper layer is uneven and has a porous structure, resulting in poor electroplating effect.

[0107] Since the preparation method of the copper foil of this invention involves an electroplating process, which requires immersion in an aqueous electroplating solution for deposition, the conductive nucleation layer on the substrate must possess both good hydrophilicity and conductivity. While existing graphene technologies share a similar two-dimensional sheet structure with MXene, conductive graphene (such as mechanically exfoliated, electrochemically processed, or reduced graphene) typically lacks hydrophilicity; and while hydrophilic graphene oxide exhibits poor conductivity, it is difficult to achieve satisfactory electroplating results when used in copper deposition processes.

[0108] In addition, the MXene material of this application differs from graphene in that: (1) the surface of the MXene material has abundant functional groups, especially halogen-containing functional groups. This can reduce the nucleation overpotential of copper deposition, promote the uniform growth of metallic copper, and obtain a dense and uniform metallic copper coating; (2) the MXene material is a transition metal carbon and / or nitride, and its constituent elements include transition metal elements. When MXene is used as a nucleating agent, the transition metal elements in it have similar metallic properties to metallic copper, which is conducive to the formation of a tightly bonded metallic copper coating.

[0109] In a specific embodiment of the present invention, MXene Ti3C2T was used. x Since MXene materials are a class of two-dimensional materials, they possess similar physicochemical properties, such as hydrophilicity, abundant surface functional groups, and conductivity. In other embodiments, other types of MXene materials, such as Ti2CT, can be substituted. x V2CT x Mo2CT x Nb2CT x Ta2CT x Ta3C2T x Ta4C3T x Ti4C3T x It is reasonable to expect that it will also be able to produce something similar to MXene Ti3C2T. x The same technical effect. The application of these different types of MXene materials in copper foil is all within the technical concept of this invention.

[0110] Example 7

[0111] This embodiment provides an electrode sheet using the copper foil of the present invention as a current collector. Specifically, the electrode sheet is a negative electrode sheet for lithium metal batteries. Molten lithium metal or lithium alloy paste is coated onto the surface of the copper foil containing a conductive MXene layer. After cooling, a lithium base layer is formed, resulting in the electrode sheet of the present invention. Figure 10As shown. The MXene in the conductive MXene layer 30 is lithiophilic, which can reduce the surface tension of molten lithium metal, allowing it to spread in the conductive MXene layer and form a lithium base layer after solidification. The thickness of the lithium base layer is between 1 μm and 100 μm, preferably between 1 μm and 10 μm.

[0112] Example 8

[0113] This embodiment provides an electrode sheet using the copper foil of the present invention as a current collector. Molten lithium metal or lithium alloy slurry is coated onto the surface of the copper layer of the copper foil of the present invention. After cooling, a lithium base layer is formed, resulting in the electrode sheet of the present invention. The thickness of the lithium base layer is between 1 μm and 100 μm, preferably between 1 μm and 10 μm. More specific steps include:

[0114] (1) Place 400mg of lithium metal in a stainless steel crucible and heat it to 350°C in an argon atmosphere in a glove box to melt the lithium metal into a liquid state.

[0115] (2) Add 40 mg of magnesium metal flakes to the liquid lithium metal, followed by 50 mg of MXene Ti3C2T. x The powder is stirred and mixed, and the magnesium sheet is melted to form a liquid lithium-magnesium alloy. Stirring is continued for about 30 minutes to achieve the desired Ti3C2T alloy composition. x Uniform dispersion yields a gel-like mixed lithium slurry;

[0116] (3) The mixed lithium slurry is coated onto the surface of the electroplated copper layer of the copper composite current collector by a scraper. After cooling, a lithium base layer is formed, resulting in an electrode sheet with a lithium base layer on the surface of the electroplated copper layer.

[0117] In other embodiments, MXene material may be added to liquid lithium metal to form a lithium metal layer.

[0118] The role of adding MXene material to liquid lithium metal or lithium alloy is to reduce the surface tension of liquid lithium metal, making it form a semi-solid (gel-like) composite that can be easily coated onto the metal composite current collector, and the thickness can be controlled to obtain an ultra-thin lithium base layer (1μm~5μm). In addition, during the charging and discharging process of lithium metal batteries, as lithium metal on the negative electrode sheet is repeatedly peeled off and deposited, the MXene material in the lithium base layer also has a nucleation effect on lithium metal, reducing the nucleation overpotential of lithium metal, controlling the nucleation sites of lithium metal with MXene, and controlling the controllable growth of lithium metal based on two-dimensional sheets, avoiding the formation of sharp lithium branches, thereby improving the safety of lithium metal batteries. Embodiments of the preparation method and technical effects of the above-mentioned ultra-thin lithium base layer are described in the applicant's patent applications with application numbers 201911241973.3 and 201911242747.7. However, using other methods, such as physical rolling, to composite lithium metal or lithium alloy onto the copper current collector of the present invention, the resulting electrode sheet is also within the technical concept of the present invention.

[0119] The electrode sheets from Example 7 or 8 are assembled into a battery, specifically, a lithium metal battery is obtained.

[0120] The lithium metal electrode sheet of the present invention can also be used in solid-state lithium metal batteries. Specifically, the electrode sheet is assembled with a solid electrolyte separator and a positive electrode sheet to obtain a solid-state lithium metal battery. In a preferred embodiment, the positive electrode material in this solid-state battery is a high-nickel ternary positive electrode material (LiNi). 0.8 Co 0.1 Mn 0.1 O2, NCM811).

[0121] The copper foil of the present invention can also replace the current copper foil current collector for use as the negative electrode current collector of lithium-ion batteries (the negative electrode material is graphite and / or silicon material). By reducing the amount of copper used, not only is the cost of the battery reduced, but the weight of the battery is also reduced, thereby improving the energy density of the lithium-ion battery.

[0122] Example 9

[0123] Since both copper foil and MXene materials possess excellent electromagnetic shielding effects, the copper foil containing a conductive MXene layer obtained in this invention can also be used as an electromagnetic shielding material in the field of electromagnetic shielding. That is, this invention also provides an electromagnetic shielding material, which is the copper foil containing a conductive MXene layer obtained in this invention. The conductive MXene layer and the copper layer can synergistically exert an electromagnetic shielding effect.

[0124] In some embodiments, the thickness of the copper substrate of the electromagnetic shielding film is between 4.5 μm and 100 μm; more preferably, between 5 μm and 50 μm; even more preferably, between 5 μm and 20 μm; the thickness of the MXene layer is between 3 nm and 50 μm; preferably, between 10 nm and 10 μm; more preferably, between 100 nm and 5 μm; even more preferably, between 200 nm and 2 μm; even more preferably, between 500 nm and 1 μm.

[0125] In a preferred embodiment, the copper base layer of the electromagnetic shielding film has a thickness of 10 μm, and the MXene layer has a thickness of 10 μm.

[0126] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A method for preparing copper foil by electroplating, characterized in that the steps include... include: Coating step: Coating at least one side of the substrate with MXene material to form a conductive MXene layer; Electroplating step: The surface of the conductive MXene layer is electroplated to form an electroplated copper layer; Stripping step: The substrate is stripped after the coating step and before the electroplating step; or, the substrate is stripped after the electroplating step.

2. The method for preparing copper foil by electroplating as described in claim 1, characterized in that, More specifically, the coating step includes: coating and / or spraying the MXene dispersion onto the surface of the substrate, and drying it to form the conductive MXene layer; And / or, the substrate is lifted from and / or impregnated in the MXene dispersion, and dried to form the conductive MXene layer.

3. The method for preparing copper foil by electroplating as described in claim 2, characterized in that, The MXene dispersion does not contain binders and / or dispersants; And / or, the MXene dispersion is composed of MXene material and solvent; And / or, the concentration of MXene in the MXene dispersion is between 0.1 mg / ml and 80 mg / ml.

4. The method for preparing copper foil by electroplating as described in claim 3, characterized in that, The solvent is selected from water and / or alcohols.

5. The method for preparing metallic copper foil by electroplating as described in claim 1, characterized in that, The thickness of the conductive MXene layer is between 3 nm and 50 μm; And / or, the thickness of the electroplated copper layer is between 10 nm and 100 μm; And / or, the thickness of the substrate is between 1 μm and 100 μm.

6. The method for preparing copper foil by electroplating as described in claim 5, characterized in that, The thickness of the conductive MXene layer is between 10 nm and 5 μm; And / or, the thickness of the electroplated copper layer is between 100 nm and 10 μm.

7. The method for preparing copper foil by electroplating as described in claim 5, characterized in that, The thickness of the electroplated copper layer is between 0.5 μm and 4 μm.

8. The method for preparing copper foil by electroplating as described in claim 1, characterized in that, The substrate is a non-conductive material.

9. The method for preparing copper foil by electroplating as described in claim 8, characterized in that, The non-conductive material is selected from polymers, ceramics, or glass.

10. The method for preparing metallic copper foil by electroplating as described in claim 9, characterized in that, The polymer is selected from one or more of acrylonitrile-butadiene-styrene copolymer, polysulfone, polycarbonate, polypropylene, phenolic resin, phenolic glass fiber reinforced plastic, nylon, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyimide, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene ether, polystyrene, polyamide, and derivatives of the above polymers.

11. The method for preparing metallic copper foil by electroplating as described in any one of claims 1 to 10, characterized in that, The preparation method further includes a passivation step: passivating the surface of the electroplated copper layer to form a protective layer.

12. A copper foil obtained by an electroplating method according to any one of claims 1 to 11.

13. The copper foil as described in claim 12, characterized in that, The thickness of the copper foil is between 100 nm and 100 μm.

14. The copper foil as described in claim 13, characterized in that, The thickness of the copper foil is between 1 μm and 10 μm.

15. The copper foil as described in claim 13, characterized in that, The thickness of the copper foil is between 1 μm and 5 μm.

16. A copper foil, characterized in that, The copper foil comprises a copper base layer and an MXene layer, wherein the copper base layer is formed by electroplating copper onto the surface of the MXene material.

17. The copper foil as described in claim 16, characterized in that, The thickness of the copper substrate is between 10 nm and 100 μm; And / or, the thickness of the MXene layer is between 3 nm and 50 μm; And / or, the copper foil has one or two copper substrates.

18. The copper foil as described in claim 17, characterized in that, The thickness of the copper substrate is between 100 nm and 10 μm; And / or, the thickness of the MXene layer is between 10 nm and 5 μm.

19. The copper foil as described in claim 17 or 18, characterized in that, The thickness of the copper substrate is between 0.5 μm and 4 μm.

20. A copper current collector, characterized in that, The method for preparing the copper current collector includes the method as described in any one of claims 1 to 11; or, the copper current collector includes copper foil as described in any one of claims 12 to 19.

21. The metallic copper current collector as described in claim 20, characterized in that, The thickness of the electroplated copper layer in the copper foil is between 1 μm and 4 μm.

22. An electrode sheet, characterized in that, Including the metallic copper current collector as described in claim 20 or 21.

23. A battery, characterized in that, Includes the copper current collector as described in claim 20 or 21; or the electrode sheet as described in claim 22.

24. An electromagnetic shielding material, characterized in that, The method for preparing the electromagnetic shielding material includes the method described in any one of claims 1 to 11; or, the electromagnetic shielding material is a copper foil as described in any one of claims 12 to 19.

25. An application of an MXene material at a polymer interface for electroplating to form a copper layer, characterized in that, The application employs the method as described in any one of claims 1 to 11.

26. An MXene material applied to polymer interfaces for electroplating to form copper layers and as a separation medium.

Citation Information

Patent Citations

  • Ultrathin metal lithium electrode, preparation method thereof, and application of ultrathin metal lithium electrode as negative electrode of primary lithium battery

    CN112928235A

  • Ultrathin lithium metal electrodes, their preparation, and their application as negative electrodes in secondary lithium batteries.

    CN112928238B

  • Flexible MXene self-supporting membrane / metal composite material and preparation method and application thereof

    CN108987674A

  • Method for manufacturing porous copper foil

    CN109825858A